Event risk covenants - Thomas Heidorn; Oliver Jaster; Ulrich Willeitner (Hochschule für Bankwirtschaft (HfB), 2001)
Merger and acquisition activities can have a strong impact on the capital structure of the companies involved and therefore on the value of debt. This paper discusses the role of covenants within debt contracts. Using the Real Option approach to quantify the implications of covenants on the value of the company, it can be shown that covenants do not necessarily reduce the risk of debt lender. The value of the company is determined by assets in place and management decisions in the future. Any limitation of the management might reduce the value of the company and therefore the value of debt.
urn:nbn:de:101:1-2008071644
Keywords: 330